IoT service distributed management architecture and service discovery method for edge-cloud federation. (20th August 2022) - Yang, Dongju; Zhang, Weida; Zhao, Zhuofeng
With the continuously increasing number of Internet of Things (IoT) services, the distributed management of IoT services becomes an inevitable trend. Under the framework of IoT edge-cloud federation framework, how to design a suitable distributed management architecture of IoT services, reduce network bandwidth overhead, reduce system latency and support the dynamic perception and rapid discovery of services are the primary problems to be solved. In this paper, the distributed management of IoT services is implemented by constructing layer-ring collaboration architecture on the cloud and edge, the service addressing channel is established on the cloud and edge using master and slave node cluster. The slave node is close to service and is dynamically aware of the service status. At the same time, the master-chord is constructed based on chord protocol among masters to enable the collaborated addressing of multiple master nodes on the cloud. So a strong service routing network on the cloud and edge is established to enable the distributed management of IoT services. This paper focuses on the service registration and discovery methods under this framework, and finally verifies the effectiveness of the method through the highway emergency scenario.